PENGARUH KUALITAS PRODUK, BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA YEO'S GREEN TEA DI KOTA BATAMm. - Agustian Candra Candra; Tiurniari Purba (LPPM Universitas Putera Batam, 2025)
In a highly competitive business world, marketing management is one of the key aspects that determines the success of a company. Marketing management encompasses various activities aimed at understanding and fulfilling consumer needs and desires. This process involves creating, communicating, and delivering value to consumers through products or services offered by the company. This study aims to determine the effect of product quality, brand image, and promotion on purchasing decisions. The method used in this study is a quantitative method with data collection through a questionnaire. The results show that hypothesis testing was carried out with the aim of providing an overview of the relationship between each independent variable, namely product quality, brand image, and promotion, affecting the dependent variable, namely purchasing decisions. The results show that product quality, brand image, and promotion have a positive and significant influence, both partially and simultaneously, on purchasing decisions for Yeo's Green Tea products in Batam City